Employer Branding as a Strategy to Attract Potential Workforce - Tikson, Shinta Dewi Sugiharti; Hamid, Nurdjanah; Mardiana, Ria (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
This research analyzes the effect of PT. Citibank Indonesia employer branding with organizational attractiveness. The organizational attractiveness that is studied in this paper are divided into two category, such as instrumental attribute and symbolic attribute. These attributes are tested further by examining the workforces’ gender and level of education. Research data is obtained through surveys, literature study, and observation. To test the hypothesis, this study uses bivariate chi square and descriptive quantitative method. Samples consist of 94 workforces which are students from three universities (Universitas Hasanuddin, Universitas Negeri Makassar, and Universitas Muslim Indonesia) in Makassar, South Sulawesi. Research shows that PT. Citibank Indonesia employer branding which consists of two organizational attractiveness (instrumental attribute and symbolic attribute) have a significant effect to attract workforce in Makassar (by gender and level of education).